Clinical and serological features of systemic sclerosis in a multicenter African American cohort: Analysis of the genome research in African American scleroderma patients clinical database. Issue 51 (December 2017) - Morgan, Nadia D.; Shah, Ami A.; Mayes, Maureen D.; Domsic, Robyn T.; Medsger, Thomas A.; Steen, Virginia D.; Varga, John; Carns, Mary; Ramos, Paula S.; Silver, Richard M.; Schiopu, Elena; Khanna, Dinesh; et al.
Abstract : Abstract: Racial differences exist in the severity of systemic sclerosis (SSc). To enhance our knowledge about SSc in African Americans, we established a comprehensive clinical database from the largest multicenter cohort of African American SSc patients assembled to date (the Genome Research in African American Scleroderma Patients (GRASP) cohort). African American SSc patients were enrolled retrospectively and prospectively over a 30-year period (1987–2016), from 18 academic centers throughout the United States. The cross-sectional prevalence of sociodemographic, clinical, and serological features was evaluated. Factors associated with clinically significant manifestations of SSc were assessed using multivariate logistic regression analyses. The study population included a total of 1009 African American SSc patients, comprised of 84% women. In total, 945 (94%) patients met the 2013 American College of Rheumatology/European League Against Rheumatism (ACR/EULAR) classification criteria for SSc, with the remaining 64 (6%) meeting the 1980 ACR or CREST (calcinosis, Raynaud's phenomenon, esophageal dysmotility, sclerodactyly, telangiectasia) criteria. While 43% were actively employed, 33% required disability support. The majority (57%) had the more severe diffuse subtype and a young age at symptom onset (39.1 ± 13.7 years), in marked contrast to that reported in cohorts of predominantly European ancestry. Also, 1 in 10 patients had a severe Medsger cardiac score of 4. Pulmonary fibrosis evident on computed tomography (CT) chest was present in 43% of patients and was significantly associated with anti-topoisomerase I positivity. 38% of patients with CT evidence of pulmonary fibrosis had a severe restrictive ventilator defect, forced vital capacity (FVC) ⩽50% predicted. A significant association was noted between longer disease duration and higher odds of pulmonary hypertension, telangiectasia, and calcinosis. The prevalence of potentially fatal scleroderma renal crisis was 7%, 3.5 times higher than the 2% prevalence reported in the European League Against Rheumatism Scleroderma Trials and Research (EUSTAR) cohort. Our study emphasizes the unique and severe disease burden of SSc in African Americans compared to those of European ancestry. Abstract : Supplemental Digital Content is available in the text